2018
DOI: 10.1016/j.actbio.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Histone-targeted gene transfer of bone morphogenetic protein-2 enhances mesenchymal stem cell chondrogenic differentiation

Abstract: This contribution addresses significant limitations in non-viral gene transfer for bone regenerative applications by exploiting a novel histone-targeting approach for cell-triggered delivery that induces osteogenic BMP-2 expression coincident with the initiation of bone repair. During repair, proliferating MSCs respond to a complex series of growth factor signals that direct their differentiation along cellular lineages essential to mature bone formation. Although these MSCs are ideal targets for enhanced tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Recently, the benefits of the H3-targeting approach were demonstrated in mesenchymal stem cell (MSC)-targeted gene delivery for bone repair applications. H3-targeted polyplexes induced a 4-fold enhancement in osteogenic bone morphogenetic protein-2 (BMP-2) expression by MSCs as compared to gene carriers lacking H3 [37]. Moreover, 100-fold more recombinant BMP-2 protein was needed to achieve similar levels of BMP-2-mediated chondrogenic gene and protein expression as H3-targeted BMP-2 gene transfer, demonstrating clear translational impacts.…”
Section: Peptides For Targeting Cells and Organellesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the benefits of the H3-targeting approach were demonstrated in mesenchymal stem cell (MSC)-targeted gene delivery for bone repair applications. H3-targeted polyplexes induced a 4-fold enhancement in osteogenic bone morphogenetic protein-2 (BMP-2) expression by MSCs as compared to gene carriers lacking H3 [37]. Moreover, 100-fold more recombinant BMP-2 protein was needed to achieve similar levels of BMP-2-mediated chondrogenic gene and protein expression as H3-targeted BMP-2 gene transfer, demonstrating clear translational impacts.…”
Section: Peptides For Targeting Cells and Organellesmentioning
confidence: 99%
“…Following endocytosis, many gene carriers become entrapped within endosomes, which can fuse with lysosomes or recycle their contents back to the cell surface. To avoid these fates, gene carriers must either escape endosomes or traffic within the cell through alternative trafficking strategies involving non-acidifying/non-recycling vesicles [36,37]. Several groups have taken advantage of the sophisticated chemical/physical properties of peptides to design peptide nanostructures with elegant membrane-disruptive capacity inside the acidic endosome.…”
Section: Peptides For Targeting Cells and Organellesmentioning
confidence: 99%
“…For example, the use of BMPs can prevent patients with genetic defects in the BMP pathway from developing nonunion and might be more effective for nonunion treatment in such patients than in those without such genetic defects. Because many studies have shown that the delivery of BMP genes as well as other genes, including vascular endothelial growth factor (VEGF), PDGF, fibroblast growth factor (FGF), Osterix, Nell-1 and Runx-2, can enhance the generation of bone both in vivo and ex vivo [19] , [20] , [21] , [22] , [23] , gene therapy might become applicable for nonunion in the foreseeable future and may represent the most useful treatment for this serious condition.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Bone morphogenetic protein 2 (BMP2), a member of the transforming growth factor beta (TGF-β) superfamily, is characterized as one of the most effective growth factors to induce MSC chondrogenic differentiation ( Kovermann et al, 2019 ; Miyazono et al, 2010 ; Munsell et al, 2018 ; Pan et al, 2008 ; Zhou et al, 2016 ). However, BMP2 is also known to induce MSC osteogenic differentiation and stimulate hypertrophic differentiation after chondrogenic differentiation, which go against maintaining of BMP2-induced cartilage phenotype ( An et al, 2010 ; Liao et al, 2014 ; Zhou et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%